Pembinaan Ekonomi Kreatif Dalam Perspektif Pendidikan Ekonomi - Hasan, Muhammad (Universitas Negeri Makassar, 2018)
This study aims to determine the effect of entrepreneurial knowledge on the creative attitude of SMEs in the sub-sector of creative economy in Kecamatan Panakkukang in the context of creative economy development. The population in this research is 129 SMEs sub-sector of creative industry. Total samples in this study were 33 samples. The results of this study showed that entrepreneurial knowledge has a positive and significant influence on the creative attitude of SMEs in creative economy sub-sector in Kecamatan Panakkukang Makassar